2020
DOI: 10.1097/ccm.0000000000004548
|View full text |Cite
|
Sign up to set email alerts
|

Higher Intensity Thromboprophylaxis Regimens and Pulmonary Embolism in Critically Ill Coronavirus Disease 2019 Patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 12 publications
1
66
1
Order By: Relevance
“… 39 41 Retrospective studies of therapeutic- compared to prophylactic-dose anticoagulation have reported mixed effects on mortality, while only two small studies have examined outcomes with intermediate- compared to prophylactic-dose anticoagulation, largely focusing on venous thromboembolism rates, again with conflicting results. 7 , 15 , 16 , 18 – 22 , 42 , 43 More recently, the ACTIV randomized clinical trial showed futility of therapeutic-compared to prophylactic-dose anticoagulation in critically ill COVID-19 patients, leading to a pause in further recruitment of critically ill patients for that trial. Our analysis is the first large-scale study to specifically examine intermediate- and prophylactic-dose anticoagulation in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 39 41 Retrospective studies of therapeutic- compared to prophylactic-dose anticoagulation have reported mixed effects on mortality, while only two small studies have examined outcomes with intermediate- compared to prophylactic-dose anticoagulation, largely focusing on venous thromboembolism rates, again with conflicting results. 7 , 15 , 16 , 18 – 22 , 42 , 43 More recently, the ACTIV randomized clinical trial showed futility of therapeutic-compared to prophylactic-dose anticoagulation in critically ill COVID-19 patients, leading to a pause in further recruitment of critically ill patients for that trial. Our analysis is the first large-scale study to specifically examine intermediate- and prophylactic-dose anticoagulation in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…96 Another study found that among 49 mechanically ventilated patients, 33% were diagnosed with PE and that the use of high intensity thromboprophylaxis was associated with a lower occurrence of PE (2/18; 11%) than a standard regimen (11/22; 50%—OR 0.13 [0.02-0.69]; p = .02). 97…”
Section: Methylprednisolone and Covid-19mentioning
confidence: 99%
“…In addition, corticosteroids (dexamethasone), antibiotics, and LMWH in a prophylactic or therapeutic dose are recommended [13]. Taccone et al documented that a high-dose regimen of thromboprophylaxis therapy may decrease the occurrence of venous thromboembolic disease in critically ill SARS-CoV-2 patients [14]. We used LMWH in a prophylactic dose due to previous exclusion of pulmonary embolism and prompt clinical improvement.…”
Section: Discussionmentioning
confidence: 99%